Photovoltaic Bus Shelter - Hiranvarodom, Somchai (Frontiers in Engineering Innovation Research, 2006)
This paper presents the design and installation of a 560 WI' stand-alone PV system to supply an electric power for a bus shelter. This system has been installed at the Faculty of Engineering in Rajamangala University of Technology Thanyaburi - RMUTT (former name was Rajamangala Institute of Technology - RIT). Klong 6 Thanyaburi district, Pathumthani province of Thailand. The purpose of this work is to study and to analyze the performance of the PV system that to be installed at the RMUTT. The university is located about 35 kilometers far from Bangkok which to be capital city of Thailand. The main reason for installing is to demonstrate the application of a PV stand-alone power system [hat is able to be used in the university or other places, not just in rural areas. The design of control circuit was experimentally done in this work. Protection of the battery from damage in terms of deep discharge and overcharge by a controller was also considered. In addition. microcontroller program for controlling the operation of LED (light emitting diode) lamps was developed to show the status of the battery's operation. During the night, an operation period of time for the fluorescent lamps. 14 x 36 watts to be installed. between 18.00 and 21.00 hours were also controlled. The system performance including the life cycle cost analysis of the system and measuring data at the design location are addressed. The results of testing are able to provide useful information for rural electrification planners to install in a particular rural school or university in Thailand. They should be applicable in other countries that are situated the same latitude angle with a similar climate. Article Details